Meningkatkan Hasil Belajar PJOK melalui Metode Demonstrasi pada Siswa Kelas VII-B SMPN 3 Masbagik Kecamatan Masbagik - Setiawati, Setiawati (MASALIQ, 2021)
Through the use of the Demonstration method, it is a concept of learning activities that help teachers carry out physical education practice learning activities by trying to maximize the active role of students, especially how students are able to carry out practical movements as explained and exemplified by the teacher. With this concept, learning outcomes are expected to be more meaningful for students. The practical learning process takes place in the form of student practice activities regarding the material discussed at that time. The quality of practical learning is more important than results. The purpose of this classroom action research (CAR) is to find out. Improving PJOK learning outcomes through the use of demonstration learning methods in class VII-B students at SMPN 3 Masbagik, Masbagik District, for the 2020/2021 academic year. In this classroom action research (CAR), it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase student learning mastery classically, namely in the first cycle by 70%, it could increase to 90% in the second cycle. The results of this classroom action research indicate that learning by applying the demonstration method can improve PJOK learning outcomes.